Managing transition risk: Toward an interdisciplinary understanding of strategies in the oil industry. (September 2022) - Blondeel, Mathieu; Bradshaw, Michael
Abstract: How actors react to change is a crucial question for social scientists interested in global energy system transformation (EST). The global oil industry's response to the challenges associated with climate change and EST is a particular topic of discussion. Here, we argue for an interdisciplinary approach, bringing together insights from multiple disciplines within the social sciences that study oil companies, to further our understanding of what they are doing and why they are doing it. Although research on the political economy and socio-technical nature of EST has led to important insights, it tends to treat the global oil industry as a monolith with common interests and strategic objectives. We argue that the analytical and conceptual tools provided by the management and business literature can help unpack this 'black box'. We explain how this is the case by exploring some of these tools and applying them to a novel heuristic, the 'Transition Strategy Continuum' that helps categorise and analyse the emerging strategies of the publicly-traded 'International Oil Companies' (IOCs). As such, we respond to the call for interdisciplinarity raised in the inaugural issue of this Journal. Ultimately, we want social scientists working on energy to take serious insights from other fields of inquiry that help illuminate the complexities of the task of transformation ahead for the IOCs and other related stakeholders.